Kedisplinan Aparatur Sipil Negara Di Dinas Sumber Daya Air Cipta Karya Dan Tata Ruang Provinsi Sumatera Utara - Panjaitan, Daniel Parluhutan; Sihombing, Sally Marisa (SAJJANA: Public Administration Review, 2023)
Discipline is the key word in the success and effectiveness of carrying out tasks in an efficient and effective manner. In an effort to improve ASN discipline, the government has issued regulations on ASN discipline, namely government regulation No. 94 of 2021. The Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province is a government agency under the responsibility of the Governor which is divided into 4 fields, namely PSJA, PJPA, Cipta Karya, Spatial Planning and 19 UPT. ASN discipline at the Water Resources, Cipta Karya and Spatial Planning Office of North Sumatra Province uses Governor Regulation No. 3 of 2021. Disciplinary problems at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province are that there are still civil servants who violate regulations, there are still civil servants who do not use time effectively, there are still civil servants who do not carry out their duties and responsibilities properly and there are still civil servants who undisciplined in attendance. This study uses a qualitative descriptive research method with the aim of research to find out and understand the discipline of ASN in the Department of Water Resources, Cipta Karya and Spatial Planning, North Sumatra Province. This research is analyzed using disciplinary theory from Malayu Hasibuan (2010: 193). The results of this study show that the discipline of ASN in the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province is that there are still many ASNs who violate the regulations at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province, so ASN must obey the regulations to increase responsibility. ASN is responsible for professionalism in work, ASN must be more effective in using time, especially in attendance and ASN performance which can be measured from the application. ASN in the Department of Water Resources and Cipta Karya work in accordance with their respective fields and positions with the percentage of good ASN performance that is not disciplined is only 3.3%, ASN absenteeism is still considered unreasonable due to the percentage value of ASN indiscipline 6.7%.